Ethnoveterinary medicinal practices in tribal regions of Andhra Pradesh, India (Bangladesh Journal of Plant Taxonomy, 2012)
The present communication deals with the plants used to treat common diseases in cattle and pet animals in the tribal belts of Andhra Pradesh, India. For the purpose of the ethnoveterinary practices, 108 plant species belonging to 99 genera and 51 families were identified. The present study reveals that leafy parts rank first, among the various plant parts used to treat different ailments of the livestock.DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10936Bangladesh J. Plant Taxon. 19(1): 7-16, 2012 (June)